The effect of transcutaneous electrical nerve stimulation (TENS) versus foam roller as recovery modalities on muscular power output - Qiu, Gao Yan (Tanjong Malim, 2024)
The effect of transcutaneous electrical nerve stimulation (TENS) versus foam roller as recovery modalities on muscular power output by Qiu, Gao Yan